Plant functional composition affects soil processes in novel successional grasslands - Yahdjian, María Laura (2017)
Secondary succession may lead to novel, exotic-dominated community states differing in structure and function from the original native counterparts. We hypothesized that grassland soil processes associated with C and N cycling decelerate with community turnover from short-lived forbs and grasses to long-lived native grasses, whereas invasion by exotic perennial grasses maintains fast cycling rates. We measured litter C and N turnover during decomposition, soil respiration, and soil N dynamics in synthetic plant communities resembling four successional stages, established on abandoned farmland in the Inland Pampa, Argentina. We also compared litter chemistry and decay rates of dominant species from each community stage in a common garden, and assessed mass loss for a standard litter type incubated in all communities. Litter decomposition and soil respiration decreased, while litter N retention increased from early through mid to late community stages dominated by forbs short-lived grasses and native perennial grasses, respectively. Soil process rates in exotic perennial grass communities were faster than in native grass communities, but similar to annual grass communities. Further, the standard litter decomposed more slowly in the native perennial than in the exotic perennial grass community. In the common garden, short-lived forbs and grasses decomposed faster than native or exotic perennial grasses, with species’ decay rates being negatively related to initial litter C : N ratio. Our results show that changes in soil processes across old-field communities arise chiefly through differences in the quality of litter produced by dominant functional groups. A dominance shift from native to exotic perennial grasses prevented the deceleration of C and N cycling expected with plant successional turnover. Thus, invasion by fast-growing exotic grasses may fundamentally alter ecosystem functioning in novel grasslands. A lay summary is available for this article.